Co-ensiling of cover crops and barley straw for biogas production. (November 2019) - Feng, Lu; Perschke, Yolanda Maria Lemes; Fontaine, Doline; Ward, Alastair James; Eriksen, Jørgen; Sørensen, Peter; Møller, Henrik Bjarne
Abstract: The study investigated the effect of co-ensiling of cover crops (CC) and barley straw (BS) on biogas production. Blends containing chopped CC and BS (mix ratios of 1:0, 2:1, 3:1, 6:1; 10:1 and 19:1 ( w:w )) were prepared and stored for 4 months prior to the biogas batch assay. Results show that CC is feasible for producing biogas with reasonable CH4 yield (330 mL CH4 gVS −1 ) and has good storability. Using of co-ensiling blends showed advantages over CC as it elevated the hydrolysis rate ( k ) from 0.024 to 0.061 d −1 and decreased the lag phase (from 5 to 0.8 days) during the thermophilic (51 °C) batch test. Synergistic effects were observed from both CH4 yield and hemi-cellulose removal. The finding provided an alternative strategy for integrated straw management and CC utilization for improved biogas production. Graphical abstract: Image 1 Highlights: Effects of co-ensiling blends and impact of synergy were investigated. Cover crop is feasible for biogas and has good storability. Anaerobic digestion of co-ensiled blend has high hydrolysis rate and low lag phase. Synergy were observed on CH4 yield and hemicellulose removal of co-ensiled blend.